Kajian Perbaikan Tegangan Menggunakan Kapasitor Bank Di PT. Panca Agung Sejati - Ibnu Hajar; Khoirunnisa Ramadhanti (Sutet, 2022)
This work study voltage correction using capacitor banks on PLN’s network distribution with medium voltage consumer of PT. Panca Agung Sejati. Voltage drop into PT. Panca Agung Sejati network in operation condition is 17.87 kV, it mean happened voltage drop in persentage of 10.65. That is not apropriate to the SPLN 72:1987 standard, that is+ 5%. While, voltage drop on the network of the company is still in the range of SPLN standard when it is not on operation by 19.67 kV (1.65%). Then, efforting to improve the voltage drop the PT. PLN (Persero) has installed capacitor banks on the network at PT. Panca Agung Sejati with a total capacity are 3 x 400 kVAR. This research simulates using ETAP 16.0 software to find out whether the capacitors are still effective for load growth in the next 10 years. Simulation result with the capacitors installed of 3 x 400 kVAR is 19.15 kV (4.25%) that is mean it has already in the range of SPLN standard. For load growth until year of 2030 will be needed five capacitors in capacity of 400 kVAR (5 x 400 kVAR) to correcting the occurred voltage drop.